Quantification of food packaging generation and material loss from major retailers in Taipei, Taiwan. (1st January 2022) - Wang, Chen-Hua; Lin, Hsin-Tien
Graphical abstract: Highlights: The material compositions of food packaging from major retailers are illustrated. The main reasons for the material loss of food packaging differs among product type. Bottled beverage contributed 49.56% of the packaging waste generation. Seafood, meat, and multilayer packaging has the highest unrecyclable ratio. Different strategies are required for diverse food types to improve recycling. Abstract: Packaging accounts for the largest demand for global plastic consumption and around 60% is for food and beverage packaging. The amount of packaging is increasing rapidly due to the expansion of retailer industries, especially in supermarkets and convenience stores. Plastic recycling strategies for food packaging in retailer industries need to be developed, but the current consumption and recycling status is not clear. To address this knowledge gap, this study quantifies the food packaging generation from major supermarket and convenience store chains in Taipei, Taiwan. We focus on the composition, recycling habit, and the recycling status to evaluate the packaging recyclability and major pathways for material losses. Based on our field survey and analysis, the total amount of plastic packaging generation was 21846.04 tons in 2020 with 64.99% of it being recycled. We defined the recycling rates as the continued product of Recyclable Content Ratio of the packaging itself, Sorting Accuracy Ratio of consumers, and Re-granulated Ratio in the final treatment facilities. These three ratios for major food categories were also presented to identify the hotspots of material losses. Our results suggest that to promote plastic food packaging recycling, identifying the limitations in different stages and designing corresponding strategies is crucial.